الحماية القانونية لبراءة الاختراع في القانون الجزائري - عبدالعالي, قاسمي (جامعة الوادي.University eloued, 2021)
استقطب موضوع براءة الاختراع اهتمام العديد من القانونيين والاقتصاديين خاصةً، لِما لها من منافع كبيرة على اقتصاديات الدول الصناعية، باعتبارها مصدرا للقوة والتفوق لها، وهو ما جعل الدول النامية تسعى بشكلٍ كبير إلى بذل الجهود من أجل الوصول إلى حلول ممكنة تُساهم بشكلٍ كبير على تطوير الاختراعات من أجل تحقيق مصالحها الاقتصادية، وهذا لا يكون إلا بالتشجيع على الاختراع والتحفيز على الإبداع التكنولوجي. "The subject of the patent has attracted the attention of many jurists and economists, in particular, because of its great benefits to the economies of industrialized countries, as a source of strength and superiority for them, which made developing countries strive to make efforts to reach possible solutions that contribute significantly to the development of inventions. In order to achieve their economic interests, and this can only be by encouraging invention and stimulating technological innovation. "
قانون أعمال
Keywords: الاختراع -التحفيز - الإبداع -التكنولوجي.; encouraging- invention - stimulating technological- innovation